Industry mark-ups and structures : the role of macroeconomic and financial structures - Mollen, Olivia Anne (Trinity College (Dublin, Ireland). Department of Economics, 2008)
This thesis is an empirical analysis of how macroeconomic and financial structures influence the performance and structure of industries, specifically manufacturing industries. It comprises of four chapters and follows a between- and within-industry analysis with the first two and latter two chapters being linked. The first chapter is a between-industry analysis of the manufacturing sectors of the U.S. and six European Union (EU-6) countries. We estimate the pricecost margins for both geographical regions and find the existence of imperfect competition in all manufacturing industries. The margins in the U.S. are generally greater than those in the EU-6. We also investigate the cyclicality of these margins and the results show that margins in the U.S. behave pro-cyclically whereas they behave counter-cyclically in the EU-6. A suggestion put forward for this is that strong union power in the EU forces wage rate increases above price increases during economic expansions but their lack of influence in the U.S. allows industries to maintain higher mark-ups.
Keywords: Economics, Ph.D.; Ph.D. Trinity College Dublin